Displacement and the public interest in Nigeria: contesting developmental rationales for displacement. Issue 3 (2nd April 2020) - Walker, Julian Hugo; Lipietz, Barbara; Ohaeri, Victoria; Onyebueke, Victor; Ujah, Oliver
ABSTRACT: The displacement of urban households and livelihoods by state institutions is typically justified on the basis of the developmental purposes of land clearance, purportedly in the public interest. However, conflicts around such displacement highlight both the contested nature of the "public interest" and the unequal position that different urban actors are into shape consensus about what this should constitute. This article draws on research into the relationship between urban infrastructure development and displacement in Nigeria, to explore how actors negotiate their positions vis-a-vis displacement and contest its developmental rationale.